2020
DOI: 10.1177/1747954120935828
|View full text |Cite
|
Sign up to set email alerts
|

Predicting elite success: Evidence comparing the career pathways of top 10 to 300 professional tennis players

Abstract: The aim of this research was to explore at what age professional tennis players at different ranking levels (top 10, 11-20, 21–50, 51–100, 101–200, 201–300) started playing tennis and had achieved their career ranking milestones, and to explore the viability of using age and ranking to predict a player’s future success. 373 top 300 ranked professional tennis players from 2010 to 2018, including 193 females (M = 32.3, SD = 3.5) and 180 males (M = 34.0, SD = 3.1) were examined. Descriptive methods and univariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
0
18
1
3
Order By: Relevance
“…Although future 51-100 and 101-175 ranked players did not have distinctive ranking signatures at these ages (Li et al 2020;Reid et al 2014), the present study showed T100 players did engage earlier in more professional competitions compared to future T250 players in late adolescence. This suggests that current selection or LTAD guidelines, anchored alone in adolescent ranking data, may oversimplify the current performance and future ranking trajectory of players.…”
Section: ***Table 2 Near Here*** Discussioncontrasting
confidence: 72%
“…Although future 51-100 and 101-175 ranked players did not have distinctive ranking signatures at these ages (Li et al 2020;Reid et al 2014), the present study showed T100 players did engage earlier in more professional competitions compared to future T250 players in late adolescence. This suggests that current selection or LTAD guidelines, anchored alone in adolescent ranking data, may oversimplify the current performance and future ranking trajectory of players.…”
Section: ***Table 2 Near Here*** Discussioncontrasting
confidence: 72%
“…After dividing the top 100 according to singles rankings into 4 intervals, the authors found RAE existence in the 76–100 positions, but they observed no RAE in other three intervals (positions 1–25, 26–50, and 51–75). In a study of top 300 ranked professional tennis players from 2010 to 2018 (193 females and 180 males) at different ranking levels, Li, Weissensteiner, Pion and De Bosscher [ 36 ] were founding out at what age the athletes had started playing tennis and when they had reached the milestones of their career ratings. It was found that 75% of the top 300 players started playing tennis between the age of 3 to 7 years and also that professional rankings between 14 and 18 years were not reliable in predicting a player’s future ranking.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the age of the players could predict the success of football clubs in the ACL. This result is not consistent with Li et al (2020). One of the possible causes of consensus is the difference in sports.…”
Section: Discussionmentioning
confidence: 63%